Monitoring Steady Flow Effects on Cell Distribution in Engineered Valve Tissues by Magnetic Resonance Imaging - Catalina Martinez; Angela Henao; Jose E. Rodriguez; Kyle R. Padgett; Sharan Ramaswamy (Molecular Imaging)
In heart valve tissue engineering, assessment of cell migration under dynamic states can provide insights on the evolving tissue structure. We labeled human vascular smooth muscle (SMCs), endothelial (ECs), and bone marrow–derived mesenchymal stem cells (BMSCs) with superparamagnetic iron oxide (SPIO) microparticles and visualized them using magnetic resonance imaging (MRI) under steady flow. We determined that vascular cells were able to remain reasonably viable and proliferate well after being labeled with SPIO microparticles (200 μg/mL) for 48 hours. SPIO-labeled cells were successfully visualized using T 2 * contrast. When physiologically representative shear stresses (5–6 dynes/cm 2 ) were applied to SMC-EC coculture–seeded scaffolds, hypointense regions seemed to have decreased after 2 weeks in some locations, whereas others revealed sustained levels of T 2 * contrast; similar observations were seen in the case of BMSC-seeded scaffolds. This could be attributable to increased out-of-plane cell migratory activity, which occurred from the fluid-induced mechanical cues received, which was not previously evidenced in static culture. Vascular cells and BMSCs were labeled with remarkably high concentrations of SPIO. Moreover, steady fluid flow enhanced intrascaffold cell migration of vascular SMCs and ECs as well as BMSCs, which, in turn, significantly improved construct cellularity and extracellular collagen content